Analysis of investment processes in health and the environment in Guyana - Whalen, Kathleen (PAHO WashingtonUS, 1993)
Reviews the evolution of the macroeconomic scenario in Guyana and its implications for the health sector. Deals with the institutional structure of the health sector and the allocation of responsibility for service delivery. Describes and analyzes the processes and procedures associated with national budgeting and capital investment and provides an inventory of health sector projects. Looks at the participation of agencies and institutions in the investment process and presents conclusions and recommendations.